2021
DOI: 10.1016/j.bja.2020.07.022
|View full text |Cite
|
Sign up to set email alerts
|

The T-type calcium channel isoform Cav3.1 is a target for the hypnotic effect of the anaesthetic neurosteroid (3β,5β,17β)-3-hydroxyandrostane-17-carbonitrile

Abstract: Background: The mechanisms underlying the role of T-type calcium channels (T-channels) in thalamocortical excitability and oscillations in vivo during neurosteroid-induced hypnosis are largely unknown. Methods: We used patch-clamp electrophysiological recordings from acute brain slices ex vivo, recordings of local field potentials (LFPs) from the central medial thalamic nucleus in vivo, and wild-type (WT) and Ca v 3.1 knockout mice to investigate the molecular mechanisms of hypnosis induced by the neurosteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 36 publications
6
38
0
Order By: Relevance
“…36 These effects of 3b-OH and TTA-P2 are either absent or severely diminished in mice lacking the Ca V 3.1 Ca 2þ channel isoform that mediates T-currents. 34,36 In conclusion, we found that 3b-OH is a potent hypnotic in rats with a rapid onset of action and an EEG signature comparable with other neurosteroid hypnotics/anaesthetics (e.g. alphaxalone).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…36 These effects of 3b-OH and TTA-P2 are either absent or severely diminished in mice lacking the Ca V 3.1 Ca 2þ channel isoform that mediates T-currents. 34,36 In conclusion, we found that 3b-OH is a potent hypnotic in rats with a rapid onset of action and an EEG signature comparable with other neurosteroid hypnotics/anaesthetics (e.g. alphaxalone).…”
Section: Discussionsupporting
confidence: 55%
“…29 Alphaxalone, a neurosteroid analogue with prominent GABAergic properties 30 that also inhibits the Ca V 3.2 Ca 2þ channel isoform of T-currents in sensory neurones, 31 is another hypnotic with a typical pattern of EEG changes. 32,33 Although 3b-OH is devoid of direct GABAergic activity in both thalamic 34 and hippocampal brain slices, 4 it produces an apparently similar EEG signature in rats. We have shown previously that 3b-OH may suppress neuronal excitability by inhibiting T-channel-dependent rebound bursting 5 and by decreasing presynaptic glutamatergic transmission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At higher concentrations above 10 μM, 3β‐OH blocks partially HVA currents and sodium currents 114 . Behavioural studies and mouse genetics of T‐channel isoforms, have shown that Ca V 3.1 and Ca V 3.2 deletion significantly decreases duration of hypnosis mediated by this neuroactive steroid when given intraperitoneally 45,46 . However, wild‐type and Ca V 3.1 and Ca V 3.2 KO still responded to toe and tail pinch, indicating that T‐channels play at least a partial role in the hypnotic effects of neuroactive steroids.…”
Section: Molecular Targets and Mechanisms Of Actionmentioning
confidence: 99%